Differentiation of partial acylglycerols derived from different animal fats by EA-IRMS and GCMS techniques - Ahmad Nizar, Nina Naquiah; Marikkar, Mohammed Nazrim; Mustafa, Shuhaimi (Instituto de la Grasa, 2016)
A study was carried out to compare partial acylglycerols of lard with those of chicken fat, beef fat and mutton fat using Gas Chromatography Mass Spectrometry (GC-MS) and Elemental Analysis–Isotope Ratio Mass Spectrometry (EA-IRMS). Mono- (MAG) and di-(DAG) acylglycerols of animal fats were prepared according to a chemical glycerolysis method and isolated by using column chromatography. The fatty acid composition and δ13C carbon isotope ratio of MAG and DAG derived from individual animal fat were determined separately to establish their identity characteristics. The results showed that the δ13C values of MAG and DAG of lard was significantly different from those of MAG and DAG derived from chicken fat, beef fat and mutton fat. According to the loading plots based on principle component analysis (PCA), fatty acids namely stearic, oleic and linoleic were the most discriminating parameters to distinctly identify MAG and DAG derived from different animal fats. This demonstrated that EA-IRMS and the PCA of fatty acid data have considerable potential in discriminating MAG and DAG derived from lard from other animal fats for Halal authentication purposes.